Reaching the people through extension publications - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Writing, editing and designing extension publications was the theme of a one-week workshop held in Port Vila, Vanuatu, from 11- 15 May 1992